Creating Connections Between Researchers and Educators. Issue 2 (15th March 2019) - O'Neil, Lauren Vega; Pakulak, Eric; Stevens, Courtney; Bell, Theodore A.; Fanning, Jessica L.; Gaston, Marci; Gomsrud, Melissa; Hampton Wray, Amanda; Holmes, Kerry B.; Klein, Scott; Longoria, Zayra; Reynolds, Mary Margaret; et al.
ABSTRACT: Translational research involving the development, implementation, and assessment of evidence-based interventions has shown promise in improving outcomes for children from lower socioeconomic-status backgrounds. One such approach involves 2-generation interventions, which target both children and their parents/caregivers. Here we traced the evolution of a 15-year partnership between researchers from the University of Oregon Brain Development Lab and educators from Head Start of Lane County, with a primary goal of developing, implementing, and evaluating a 2-generation intervention. The partnership has produced a successful 2-generation intervention, with current efforts focused on the development of a scaled-up delivery model that can be implemented by Head Start staff and integrated into existing Head Start structure classrooms. Taking a "lessons-learned" approach and including the perspectives of researchers and educators, we highlight 4 key themes that emerged from this partnership and may be useful to other researchers collaborating with educators to develop evidence-based interventions: 1) employ smaller-scale studies that trade ecological validity for experimental control to establish a proof of concept, 2) adapt to real-world constraints when scaling for broader implementation, 3) consider theoretical insights from smaller-scale studies when developing scalable delivery models, and 4) work together to find novel solutions to common problems. We close with results from a survey of teachers involved in the project, a broad reflection on successes of the collaboration, and a discussion on focusing efforts to sustain the intervention in the future.